(untitled) (Education in the 21st Century, 2025)
In the continuously evolving and complex system of higher education, effective management and the assurance of high-quality education require constant analysis of ongoing processes within the system, as well as solutions to existing (“permanent”) or newly emerging diverse issues. In this regard, special importance is given to monitoring, which, on the one hand, is viewed as a tool for studying and evaluating the current situation and realities, and on the other hand, as a vital means of obtaining the necessary information to ensure the advancement of the educational institution. Quality monitoring in education is one of the key prerequisites for enhancing the effectiveness of education system management and improving learning processes. This article attempts to emphasize the role of monitoring in the field of education, particularly in higher education. Using the example of Yerevan State University (YSU), it comprehensively examines and presents the processes of implementing monitoring of study programs (SPs) , identifying necessary actions for improving these programs based on the results, and planning and executing measures that ensure the effectiveness of these actions.